Complement activation by an angiogenic imbalance leads to systemic vascular endothelial dysfunction: A new proposal for the pathophysiology of preeclampsia. (June 2021) - Matsuyama, Tatsuya; Tomimatsu, Takuji; Mimura, Kazuya; Yagi, Kazunobu; Kawanishi, Yoko; Kakigano, Aiko; Nakamura, Hitomi; Endo, Masayuki; Kimura, Tadashi
Highlights: Relationship between complement activation and angiogenic imbalance remains unclear. Complement factor H (CFH) protects endothelial cells from complement activation. PlGF promotes the expression and secretion of CFH in endothelial cells, but sFlt1 reverses these effects. This novel mechanism may pave the way for new treatment strategies for preeclampsia. Abstract: The underlying mechanism of preeclampsia by which an angiogenic imbalance results in systemic vascular endothelial dysfunction remains unclear. Complement activation directly induces endothelial dysfunction and is known to be involved in preeclampsia; nevertheless, the association between complement activation and angiogenic imbalance has not been established. This study aimed to evaluate whether angiogenic imbalance affects the expression and secretion of inhibitory complement factor H (CFH) in endothelial cells, resulting in complement activation and systemic vascular endothelial dysfunction. Viability of human umbilical vein endothelial cells (HUVECs) was assessed upon CFH knockdown by targeted-siRNA, and were incubated with complement factors. HUVECs were also treated with placental growth factor (PlGF) and/or soluble fms-like tyrosine kinase 1 (sFlt1), and CFH expression and secretion were measured. These cells were evaluated by cell viability assay and cell surface complement activation was quantified by immunocytochemical assessment of C5b-9 deposition. HUVECs transfected with CFH-siRNA had significantly lower viability than that of control cells. Moreover, the expression and secretion of CFH were significantly increased upon PlGF treatment compared with PlGF + sFlt1 combo. HUVECs treated with PlGF had less C5b-9 deposition and higher viability than HUVECs treated with PlGF + sFlt1. In summary, CFH was found to be essential for endothelial cell survival by inhibiting complement activation. An angiogenic imbalance, including decreased PlGF and increased sFlt1, suppresses CFH expression and secretion, resulting in complement activation on the surface of endothelial cells and systemic vascular endothelial dysfunction.